2021
DOI: 10.5435/jaaos-d-20-00464
|View full text |Cite
|
Sign up to set email alerts
|

Performing a Safe and Effective Total Hip Arthroplasty on Patients With Inactive or Stably Active Systemic Lupus Erythematosus With Osteonecrosis

Abstract: Introduction: Patients with systemic lupus erythematosus (SLE) are typically treated with total hip arthroplasty (THA) because of osteonecrosis of the femoral head (ONFH). This study evaluated the outcome of THA in this patient group. Methods: From January 2004 to January 2017, we retrospectively studied 92 THAs for patients with SLE and 92 THAs for age- and sex-matched patients suffering from ONFH due to nonrheumatic etiologies Both groups were treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Demographics and clinical outcomes were summarized in Tables 1 Tables 2. Among the ten screened citations, seven were the case-control studies [7,11,14,15,17,23,24], two were retrospective [18,25], and one was cohort studies a study [10]. A total of 29573 hips in the SLE group were studied compared to 4013027 hips in the non-SLE group.…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Demographics and clinical outcomes were summarized in Tables 1 Tables 2. Among the ten screened citations, seven were the case-control studies [7,11,14,15,17,23,24], two were retrospective [18,25], and one was cohort studies a study [10]. A total of 29573 hips in the SLE group were studied compared to 4013027 hips in the non-SLE group.…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
“…Wound infection. The wound infection was used in seven studies [10,11,14,15,17,23,24], and the results in the metaanalysis showed signi cant differences. According to Fig.…”
Section: Complicationmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it is generally believed that patients with systemic lupus erythematosus could have good final function after THA, controversies remain with regard to whether patients with lupus have more complications after undergoing THA. Some case-control studies have shown that SLE patients have a higher incidence of perioperative complications and longer hospital stay during the perioperative period of total hip arthroplasty than patients with rheumatoid arthritis or osteoarthritis [8][9][10][11][12][13][14]. Some studies have reported that SLE is not an independent risk factor for perioperative adverse events in THA.…”
Section: Introductionmentioning
confidence: 99%